Diurnal use of time and space by breeding Blue Duck Hymenolaimus malacorhynchos - Veltman, Clare J; Williams, Murray (Wildfowl, 1990)
The diurnal time-activity budgets of two territorial pairs of Blue Duck were measured during the breeding season in New Zealand from August to December 1986. Morning and evening peaks of foraging behaviour characterised pre-incubation time budgets but their absence during and after the incubation phase indicated that Blue Duck activity was not determined by temporal variations in prey availability. Foraging accounted for less than 20% of the males' active day during all phases of the breeding cycle, except when moulting, whereas females spent over half their day feeding prior to laying. Males and females invested equal time in the major activity classes when ducklings were present. Home ranges contracted around the nest site during incubation and moulting, but encompassed the entire territory when ducklings were present. Blue Ducks predominantly used the river's edge and varied their behaviour in relation to other physical characteristics of the river. We conclude that defence of a food supply is not the primary function of year-round territoriality in Blue Ducks.